MEMAKSIMALKAN POTENSI BISNIS INTERNET PADA JARINGAN NIRKABEL (Studi Kasus: Pengembangan Jaringan Lan di Pondok Pesantren Terpadu Al Mumtaz - Setiadi, Yuki Syambudi; Raharjo, Suwanto; Triyono, Joko (Jurnal Jarkom, 2014)
ABSTRACTWireless technology, has now spread all-over the nation. By using radio waves, wireless technology on computer network becomes indicate its existence compare to conventional network model (wired network). The existence of technology which becomes cheaper, has support the existence of these wireless network also. Nowadays, areas supported with wireless network or often called hotspot become easier to find. The cheaper the devices to build these hotspot networks, has passionate peoples to use this business opportunity on wireless network. Many tricks use by businessman, start with obligation to buy good before using hotspot facility until âWarung Internetâ AKA âWARNETâ. But, using prepaid cards AKA vouchers are the most prospective business strategy. This occurs because it simplicity to manage on businessmanâs side and it simplicity on customerâs side. Consider to the target of PT. Telkom which obsessed to make Indonesia becomes nation with the largest numbers of WiFi area in Asia (Yandi, 2012), it is 10 millions WiFi radio at 2015, is certainly hotspot business is one of the âhottestâ business in future. But thus, hotspot business must be controlled so it doesnât cross-side with law and norm, moreover if this business runs within Islamic Boarding Schoolâs environment. With some synchronization between the system and Islamic Boarding Schoolâs ideology, then this hotspot business will becomes really useful for the instance.Â Keywords: Hotspot, Voucher, Ideology, Islamic Boarding School